2019
DOI: 10.1177/2515841419892056
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of optical coherence tomography angiography results of adult patients with Familial Mediterranean fever and healthy individuals

Abstract: Purpose:The aim of this study is to assess the macular ultrastructure measuring by optical coherence tomography angiography in adult patients with Familial Mediterranean fever.Methods:Participants were 62 Familial Mediterranean fever patients and 54 healthy individuals in control group with similar age and sex. The superficial and deep vascular plexus structures covering the central fovea in an area of 6 mm × 6 mm were measured using AngioVue images taken with optical coherence tomography angiography. Vasculat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 32 publications
1
4
0
Order By: Relevance
“…We found that the DCP-VDs in the parafovea, superior hemi, temporal, and superior regions were low in the patients with FMF. Similarly to our study, deep inferior and deep inferior hemi VDs have been reported to be significantly decreased in patients with FMF than in healthy controls (14) . These results suggest that deep retinal microvascular structures may be more susceptible to inflammation.…”
supporting
confidence: 91%
See 1 more Smart Citation
“…We found that the DCP-VDs in the parafovea, superior hemi, temporal, and superior regions were low in the patients with FMF. Similarly to our study, deep inferior and deep inferior hemi VDs have been reported to be significantly decreased in patients with FMF than in healthy controls (14) . These results suggest that deep retinal microvascular structures may be more susceptible to inflammation.…”
supporting
confidence: 91%
“…In previous studies, mostly case reports, that examined eye findings in patients with FMF, ocular findings such as uveitis, retinal diseases, amaurosis fugax, optic neuritis, and ocular surface and tear film abnormalities have been reported during attacks in the patients with FMF (10)(11)(12)(13) . However, when the literature is examined, a limited number of studies were on retinal and choroidal vascular changes in patients with FMF (14) .…”
Section: Introductionmentioning
confidence: 99%
“…Karaca et al compared the retinal vascular densities of 62 FMF patients with those of 54 healthy individuals. In their study, they found that the mean DCP inferior quadrant PAFVD and the mean DCP inferior-hemi quadrant vascular density of the FMF patients were statistically signi cantly lower than those of the control group (p=0,04, p=0,03, respectively)[10].In our study, we found that the mean DCP TVD and mean DCP PAFVD of the FMF patients were statistically signi cantly lower than those of the control group (p=0,045, p=0,034, respectively). Also, there was a statistically signi cant negative correlation between the duration of FMF disease and DCP total vascular density, DCP Parafoveal vascular density, and DCP Perifoveal vascular density.…”
mentioning
confidence: 89%
“…OCTA can detect motion contrast in blood ow and evaluate both super cial and deep vascular density at macular capillary plexus [8]. Previous studies detected changes in retinal vascular blood ow in FMF patients through OCTA [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…The clinical presentation of FMF and TRAPS is similar and characterized by recurrent fever, erysipelas-like or erythematous skin rash, serositis, arthralgia, myalgia, and lymphadenopathy. The most frequent ocular findings are choroidal thickening, retinal vasculitis and anterior uveitis ( 118 , 121 – 126 ).…”
Section: Non-infectious Uveitismentioning
confidence: 99%